2018
DOI: 10.1103/physreve.97.022604
|View full text |Cite
|
Sign up to set email alerts
|

Waterlike anomalies in a two-dimensional core-softened potential

Abstract: We investigate the structural, thermodynamic, and dynamic behavior of a two-dimensional (2D) core-corona system using Langevin dynamics simulations. The particles are modeled by employing a core-softened potential which exhibits waterlike anomalies in three dimensions. In previous studies in a quasi-2D system a new region in the pressure versus temperature phase diagram of structural anomalies was observed. Here we show that for the two-dimensional case two regions in the pressure versus temperature phase diag… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

6
17
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
7
2

Relationship

2
7

Authors

Journals

citations
Cited by 25 publications
(23 citation statements)
references
References 80 publications
6
17
0
Order By: Relevance
“…A consequence of the anomalies in the phase diagram is the presence of a reentrant liquid phase and a transition from the well defined hexagonal lattice to an amorphous stripe-like structure. This ordered-disordered transition was observed in previous works where particles interact through two length potentials also known as the ramp-like potentials [30,33,49]. In the previous works as here the anomalies arise from the competition between the two length scales.…”
Section: A Polymer-grafted Nanoparticles With Fixed Polymerssupporting
confidence: 75%
See 1 more Smart Citation
“…A consequence of the anomalies in the phase diagram is the presence of a reentrant liquid phase and a transition from the well defined hexagonal lattice to an amorphous stripe-like structure. This ordered-disordered transition was observed in previous works where particles interact through two length potentials also known as the ramp-like potentials [30,33,49]. In the previous works as here the anomalies arise from the competition between the two length scales.…”
Section: A Polymer-grafted Nanoparticles With Fixed Polymerssupporting
confidence: 75%
“…Experiments [25] and simulations [26,27] showed that in the case of spherical colloids the mechanism behind the formation of these distinct patterns is the presence of competitive interactions. These com-peting forces can appear from the combination of a short range attraction of the core and a long-range repulsion [28] of the grafted polymers [29][30][31][32][33][34].…”
Section: Introductionmentioning
confidence: 99%
“…36,[38][39][40] The flexibility to simulate a wide range of anomalous systems by changing the relative strength of two and three body terms has made the SW potential a key model for studying this behavior although soft-core potentials have also been successfully employed. [41][42][43][44][45][46][47][48][49][50][51][52] Although some of the work referenced above 29 employs methods to push the limits of metastability (by employing replica exchange techniques, for example), the anomalies in deeply supercooled regions of the phase space have not been reported in literature to date (in particular, in the low temperature limit). Related investigations, using the SW potential have studied the progression of the anomalous behavior as a function of the strength of the three body term by fitting the thermodynamic results to a two state model.…”
Section: Introductionmentioning
confidence: 99%
“…The property (iii) resembles recent results for other confined anomalous-fluid models where it was attributed to the competition of two interaction length-scales, 10,95 the appearance of amorphous phases 95 or the reentrance of the melting line. 96 However, here we find it also for the simple fluid without competing length-scales, amorphous phases or reentrant melting, showing that the presence of confinement is enough to get the property (iii), as well as the (i) and (ii), in the three fluids.…”
Section: Dynamicsmentioning
confidence: 54%